1998
DOI: 10.1111/j.1600-0447.1998.tb10004.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of excitatory amino acids, serine, glycine, histidine, threonine, taurine, alanine and arginine in treatment‐resistant depression: modulation by treatment with antidepressants and prediction of clinical responsivity

Abstract: Previous research has revealed that major depression is accompanied by disorders in excitatory amino acids, e.g. glutamate and aspartate, and alterations in serum levels of other amino acids, e.g. serine, glycine and taurine. The aim of the present study was to examine serum levels of aspartate, asparagine, glutamate, glutamine, serine, glycine, threonine, histidine, alanine, taurine and arginine in major depression patients with treatment-resistant depression (TRD). No significant differences in the serum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
1
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(99 citation statements)
references
References 27 publications
4
88
1
6
Order By: Relevance
“…Increased activity of the glutamatergic system in the peripheral blood of depressive patients has been repeatedly shown [69,70,71], although this result could not be replicated by all groups [72]. The inconsistency of the findings, however, might be due to methodological problems [73].…”
Section: Inflammation Influences the Metabolism Of Serotonin And Noramentioning
confidence: 91%
“…Increased activity of the glutamatergic system in the peripheral blood of depressive patients has been repeatedly shown [69,70,71], although this result could not be replicated by all groups [72]. The inconsistency of the findings, however, might be due to methodological problems [73].…”
Section: Inflammation Influences the Metabolism Of Serotonin And Noramentioning
confidence: 91%
“…20,21 Several studies showed an increased activity of the glutamatergic system in the peripheral blood of depressive patients, [22][23][24] although this result could not be replicated by all authors. 25 The inconsistency of the findings, however, might be due to medication effects, low statistical power and a lack of appropriate control of diagnosis. 9 Support for increased glutamatergic activity in depression comes from magnetic resonance spectroscopy: elevated glutamate levels were found in the occipital cortex of unmedicated subjects with MD.…”
Section: Glutamate In Depressionmentioning
confidence: 99%
“…Specifically, it has been shown that glutamate metabolism differs significantly between depressed patients and controls when assessing glutamate and/ or glutamine levels in plasma or cerebrospinal fluid and when examining platelet intracellular Ca 2+ release in response to glutamate stimulation (66 -70). Furthermore, some of these differences have been resolved by chronic antidepressant treatments (71,72). Magnetic resonance imaging methods have shown reduced glutamate levels in the anterior cingulate cortex (73,74), which were returned to normal levels following successful antidepressant treatments (74,75).…”
Section: Glutamate and Depressionmentioning
confidence: 99%